2016
DOI: 10.1002/ajcp.12067
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Predictors of Housing Stability, Housing Quality, and Mental Health Functioning Among Single Homeless Individuals Staying in Emergency Shelters

Abstract: The current study examined risk and resilience factors at multiple levels that affect homeless individuals' ability to exit homelessness and achieve housing stability. It also examined the relationship between housing status, housing quality and mental health functioning. The methodology is a longitudinal study of single homeless individuals staying in emergency shelters in a medium-sized Canadian city who were followed for a 2 year period. Data were collected from participants at a baseline interview when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 44 publications
5
39
0
3
Order By: Relevance
“…(2014) and subsequently used as modified scale in other studies (O'Campo et al., 2016; Patterson et al., 2014; Stergiopoulos et al., 2016). Other standardised scales used in full or in part to measure CI included: Lehman's Quality of Life Interview (Lehman, 1983; n = 2; 9.5%; O'Connell et al., 2017; Wood et al., 1998); Social Provisions Scale (Cutrona & Russell, 1987; n = 2; 9.5%; Pankratz et al., 2017; Stewart et al., 2009); ASR (Achenbach, 1997; n = 2; 9.5%); Multnomah Community Ability Scale (Hendryx, Dyck, McBride, & Whitbeck, 2001; n = 1; 4.8%; Aubry et al., 2016); UCLA‐LS‐R (Russell et al., 1980; n = 1; 4.8%; Stewart et al., 2009); SCS‐R (Lee et al, 2001; n = 1; 4.8%; McCay et al., 2011); MOS‐SSS (Sherbourne & Stewart, 1991; n = 1; 4.8%; Boisvert et al., 2008); and ASI (McLellan et al, 1992; n = 1; 4.8%; Devine et al., 1997). Although some of these scales were designed to measure constructs other than CI (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…(2014) and subsequently used as modified scale in other studies (O'Campo et al., 2016; Patterson et al., 2014; Stergiopoulos et al., 2016). Other standardised scales used in full or in part to measure CI included: Lehman's Quality of Life Interview (Lehman, 1983; n = 2; 9.5%; O'Connell et al., 2017; Wood et al., 1998); Social Provisions Scale (Cutrona & Russell, 1987; n = 2; 9.5%; Pankratz et al., 2017; Stewart et al., 2009); ASR (Achenbach, 1997; n = 2; 9.5%); Multnomah Community Ability Scale (Hendryx, Dyck, McBride, & Whitbeck, 2001; n = 1; 4.8%; Aubry et al., 2016); UCLA‐LS‐R (Russell et al., 1980; n = 1; 4.8%; Stewart et al., 2009); SCS‐R (Lee et al, 2001; n = 1; 4.8%; McCay et al., 2011); MOS‐SSS (Sherbourne & Stewart, 1991; n = 1; 4.8%; Boisvert et al., 2008); and ASI (McLellan et al, 1992; n = 1; 4.8%; Devine et al., 1997). Although some of these scales were designed to measure constructs other than CI (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…A previous analysis of data from this study showed that the increases in social network size observed among participants who received a housing voucher were largely attributable to increased numbers of peer relationships, rather than increased numbers of family relationships (O'Connell et al, ). Larger social networks, regardless of composition, may allow individuals to rely upon a diverse array of supports needed to exit homelessness (Aubry, Duhoux, et al., ). In light of other research which shows that the quality of relationships developed may be more important than the quantity of interactions for quality of life (Hawkins & Abrams, ), supported housing programs should do more than just provide opportunities to participate in activities—but may want to focus on the development of supportive relationships with others, especially peers, who can be sources of emotional support.…”
Section: Discussionmentioning
confidence: 99%
“…In supported housing research, the degree to which a person experiences an emotional connection with and membership in one's community (i.e., psychological integration (Wong, )) has been associated with greater social support and cohesion, quality of housing, more positive interactions with neighbors, sense of belonging, and ontological security (Cherner, Aubry, & Ecker, ; Ecker & Aubry, , ; Nemiroff, Aubry, & Klodawsky, ; Padgett, ; Prince & Prince, ; Yanos, Felton, Tsemberis, & Frye, ). Other research suggests that having interpersonal and community resources, and especially, having a larger social support network, access to subsidized housing, and greater income were associated with greater residential stability (Aubry, Duhoux, Klodawsky, Ecker, & Hay, ). Support from family and friends (Caton et al., ; O'Connell & Rosenheck, ; Zlotnick, Tam, & Robertson, ) and support from service providers (Patterson, Currie, Rezansoff, & Somers, ) appear to be important resources that contribute to leaving homelessness.…”
Section: Introductionmentioning
confidence: 99%
“…Greater choice and control over housing and support has been shown to be an important contributor to wellbeing and quality of life of people with lived experience of mental ill health (Nelson et al 2007). Autonomy with respect to housing aspirations, and any housing situation that fosters the development of meaningful relationships in the home and community are associated with improved wellbeing and quality of life, and decreased symptomatology and service use (Aubry et al 2016;Nelson et al 2007).…”
Section: Links Between Housing and Mental Healthmentioning
confidence: 99%